2018
DOI: 10.1097/imi.0000000000000487
|View full text |Cite
|
Sign up to set email alerts
|

Totally Endoscopic Resection of Giant Left Atrial Myxoma without Robotic Assistance

Abstract: There was no report on the application of totally endoscopic surgery for giant atrial myxoma resection. A 62-year-old female patient with giant atrial myxoma causing severe mitral stenosis and acute pulmonary edema underwent a successful operation by totally endoscopic techniques without the assistance of robotic systems using four small trocar ports (three 5-mm trocars and one 12-mm trocar). The patient recovered uneventfully and was satisfied with cosmetic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
0
7
0
2
Order By: Relevance
“…In a recently published small study from Bangladesh, all 20 patients with cardiac myxoma survived the surgery, and 1 patient presented with recurrence 28 mo after the surgery[ 111 ]. In recent years, cardiac myxomas have been excised successfully by minimally invasive surgery with or without robotic assistance[ 119 - 122 ]. Robotic surgery has been associated with early restoration of normal quality of life and early return to employment[ 121 ].…”
Section: Treatmentmentioning
confidence: 99%
“…In a recently published small study from Bangladesh, all 20 patients with cardiac myxoma survived the surgery, and 1 patient presented with recurrence 28 mo after the surgery[ 111 ]. In recent years, cardiac myxomas have been excised successfully by minimally invasive surgery with or without robotic assistance[ 119 - 122 ]. Robotic surgery has been associated with early restoration of normal quality of life and early return to employment[ 121 ].…”
Section: Treatmentmentioning
confidence: 99%
“…However direct FA cannulation is the standard technique, it predispose the small patients to some risks: (1) the pressure of the arterial line may increase gradually during the operation due to the reflex arterial spasm, especially in children, (2) acute lower limb ischaemia during and after surgery, and (3) postoperative stenosis of the iliac or femoral arteries [6]. As in our other reports [[7], [8], [9]], we used a Knitted Dacron graft (Vascutek Terumo, Bangkok, Thailand) to connect to the common FA of the patient with an end-to-side anastomosis. At the end of the operation, the graft was cut as near as possible to the anastomosis.…”
Section: Discussionmentioning
confidence: 59%
“…We chose complete sternotomy even though minimally invasive or endoscopic excision of atrial myxomas with or without robotic assistance has been reported. 12,13 Full sternotomy not only is the most straightforward approach in a hemodynamically compromised patient with an unusually large tumor but also improves visualization of the operating field, and facilitates dealing with any complications such as bleeding or need to address the tricuspid valve. Retrospectively, our decision to perform a full sternotomy also allowed us to inspect the tricuspid valve and evaluate the situation in terms of the need for cardioplegic arrest.…”
Section: Discussionmentioning
confidence: 99%